(untitled) (Intent Research Scientific Journal, 2023)
Relevance. Immunoprophylaxis is one of the effective measures to combat infectious diseases. Significant progress in the fight against infectious diseases is associated with vaccination, and this is the basis for the prospects for the complete elimination of certain infectious diseases.